Research progress and hotspot analysis of rhizosphere microorganisms based on bibliometrics from 2012 to 2021 - Sun, Shangsheng; Xue, Ruipeng; Liu, Mengyue; Wang, Liqing; Zhang, Wei (Frontiers in Microbiology, 2023)
Rhizosphere microorganisms are important organisms for plant growth promotion and bio-control. To understand the research hot topics and frontier trends of rhizosphere microorganisms comprehensively and systematically, we collected 6056 publications on rhizosphere microorganisms from Web of Science and performed a bibliometric analysis by CiteSpace 6.1.3 and R 5.3.1. The results showed that the total number of references issued in this field has been on the rise in the past decades. China, India and Pakistan are the top three countries in terms of the number of articles issued, while Germany, the United States and Spain were the countries with the highest number of co-published papers with other countries. The core research content in this field were the bio-control, bacterial community, ACC deaminase, phytoremediation, induced systematic resistance, and plant growth promotion. Seeding growth, Bacillus velezensis, plant-growth and biological-control were currently and may be the highlights in the field of rhizosphere microorganisms research for a long time in the future. The above study results quantitatively, objectively and scientifically described the research status and research focus of rhizosphere microorganisms from 2012 to 2021 from the perspective of referred papers, with a view to promoting in-depth research in this field and providing reference information for scholars in related fields to refine research trends and scientific issues.